The regulating role of miR-494 on HCCR1 in cervical cancer cells - Zheng, Ziwen; Yang, Xiaorong; Yu, Qinde; Li, Ling; Qiao, Li (Cellular and Molecular Biology, 2022)
This study focused on miR-494 inhibiting the proliferation, migration and invasion of cervical cancer cells by regulating HCCR1. During the study, 30 pairs of primary cervical cancer tissues and adjacent tissues diagnosed by pathology were collected, and then placed in a cryopreservation tube, immediately placed in liquid nitrogen to freeze, and then moved to a -80 °C refrigerator for storage until use. They were dipped with crystal violet staining solution for 20 minutes, washed 3 times with PBS, and dried at room temperature. The polycarbonate film on the chamber was gently cut, placed on a glass slide, and covered with neutral resin. The number of cells in 5 random fields was counted under a microscope, and the differences between the groups were compared. The qRT-PCR results showed that compared with the normal cervical tissue cell line HCCR1, the expression levels of miR-494 in cervical cancer cell lines HCCR1 and C-33A were significantly reduced. Compared with the transfection of mimics NC, the level of HCCR1mRNA and protein decreased significantly when transfected with miRNA-494mimics (P <0.05); compared with the transfection of inhibitor NC, the level of HCCR1 mRNA and protein increased significantly when transfected with miRNA-494 inhibitor (P <0.05).